2006
DOI: 10.1207/s15374424jccp3501_4
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Behavior Dimensions and Child Psychopathology: Specificity, Task Dependency, and Interactive Relations

Abstract: This study examined the specificity of relations between parent / caregiver behaviors and childhood internalizing and externalizing problems in a sample of 70 fourth grade children (64% male, mean age = 9.7 years). Specificity was assessed via (a) unique effects, (b) differential effects, and (c) interactive effects. When measured as unique and differential effects, specificity was not found for warmth or psychological control but was found for caregiver's use of behavior control. Higher levels of behavior con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
115
2
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(136 citation statements)
references
References 59 publications
13
115
2
6
Order By: Relevance
“…As recently noted by Caron et al (2006), third variables must be controlled to conclude with confidence that a parenting behavior is related to a specific child outcome. In essence, by controlling for third variables (e.g., a second parenting behavior and/or a co-occurring child outcome), a unique effect between a parenting behavior and a child outcome can be specified.…”
Section: Individual Parenting Behaviorsmentioning
confidence: 99%
See 4 more Smart Citations
“…As recently noted by Caron et al (2006), third variables must be controlled to conclude with confidence that a parenting behavior is related to a specific child outcome. In essence, by controlling for third variables (e.g., a second parenting behavior and/or a co-occurring child outcome), a unique effect between a parenting behavior and a child outcome can be specified.…”
Section: Individual Parenting Behaviorsmentioning
confidence: 99%
“…Unfortunately, however, in the relatively small number of studies that have tested interactions, significant findings, such as those reported by Weaver and Prelow (2005) and Forehand and Nousianinen (1993), have rarely materialized (Barber, Olson, & Shagle, 1994;Galambos et al, 2003;Garber et al, 1997;Kurdek & Fine, 1994;Stice, Barrera, & Chassis, 1993). Caron et al (2006) proposed that examining interactions is one way to test for specificity, as interactions reveal whether a given parenting behavior is related to a given child outcome across all levels of a second parenting behavior (diffuse association) or only at particular levels of the second parenting behavior (specific association). However, consistent with the majority of studies reviewed in the previous paragraph, neither Caron et al (2006) nor Jones et al (2007) found a significant interaction between warmth and behavioral control.…”
Section: Interactions Between Parenting Behaviorsmentioning
confidence: 99%
See 3 more Smart Citations